Workplace loneliness mediates the relationship between perceived organizational support and job performance: Differing by extraversion - Tian, Guomei; Liu, Tingting; Yang, Ruo (Frontiers in Psychology, 2023)
Drawing on the conservation of resources (COR) theory and social cognitive theory (SCT), we developed a moderated-mediation model to examine the mediating role of workplace loneliness in the relationship between perceived organizational support and job performance, as well as the moderating role of extraversion in such relationships. A total of 332 full-time Chinese employees from various enterprises voluntarily participated in the two-wave surveys via either paper-and-pencil or online survey conducted at Credamo and Tencent Questionnaire website. Hierarchical regression and bootstrapping analyses were employed to examine the hypotheses. Results indicated that workplace loneliness partially mediates the linkage between perceived organizational support and job performance; extraversion serves as a moderator in the relationship between workplace loneliness and job performance, as well as the mediating role of workplace loneliness linking perceived organizational support to job performance, such that the relationship is stronger when extraversion is high. Supplementary analyses revealed that social companionship, but not emotional deprivation, serves a mediator in the relationship between perceived organizational support and job performance; extraversion enhanced the direct influence of social companionship on job performance, as well as the indirect influence of perceived organizational support on job performance via social companionship. Theoretical and practical implications are discussed.